2012
DOI: 10.1063/1.4731790
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative study of the interfacial intermixing and segregation effects across the wetting layer of Ga(As,Sb)-capped InAs quantum dots

Abstract: Wetting layer states of In As ∕ Ga As self-assembled quantum dot structures: Effect of intermixing and capping layer Quantitative analysis of compositional changes in In Ga As ∕ In Ga As P quantum wells on GaAs induced by intermixing with a low temperature grown InGaP cap layer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Moreover, a slight interface broadening (≈0.5-1.0 ML) is introduced by the need to orient the interface slightly away from the edge-on condition in order to bring the 002 reflection close to the Bragg condition. [19] Despite these practical concerns, it is significant that the present estimates of interfacial width made using the g 002 DFTEM technique are similar to measurements from other materials systems using different methods, such as EELS [19,27] or atom probe tomography. [28,29] For example, a Z-contrast imaging study of interfacial intermixing in InAs/GaSb NCA superlattices indicated interfacial widths (10-90% criterion) of 2.69 and 2.11 ML at InAs-on-GaSb and GaSb-on-InAs interfaces, respectively.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, a slight interface broadening (≈0.5-1.0 ML) is introduced by the need to orient the interface slightly away from the edge-on condition in order to bring the 002 reflection close to the Bragg condition. [19] Despite these practical concerns, it is significant that the present estimates of interfacial width made using the g 002 DFTEM technique are similar to measurements from other materials systems using different methods, such as EELS [19,27] or atom probe tomography. [28,29] For example, a Z-contrast imaging study of interfacial intermixing in InAs/GaSb NCA superlattices indicated interfacial widths (10-90% criterion) of 2.69 and 2.11 ML at InAs-on-GaSb and GaSb-on-InAs interfaces, respectively.…”
Section: Discussionmentioning
confidence: 79%
“…24 In addition, although this imaging method is aperture-limited, it has been shown elsewhere that detailed analysis of the shape of the composition profiles, supported by structural modeling, allows quantification of the chemical interface, and variations in interface widths and layer thicknesses as small as 0.1 ML can be measured. 25,26…”
Section: Dark-field Imagingmentioning
confidence: 99%
“…This is unlikely to be due to Sb segregation; rather, this non-ideal interface is due to an intrinsic minimum interface width that is dictated by the moleculessurface interaction potential during growth, and can be approximated with a set of sigmoidal functions, as represented by Equation (3). [24][25][26] For layers centered at z ¼ 0, the sigmoidal expressions are…”
Section: Evaluation Of Antimony Segregationmentioning
confidence: 99%